The Piano in Barquisimeto: Memory, Institutions, and Pedagogies: Contributions to the Musical Historiography of Lara State (1860–2000) (Mayéutica Revista Científica de Humanidades y Artes, 2026)
In Barquisimeto, the piano has had the same social importance as in the rest of the world. However, there is a lack of research and studies on the social and artistic practices surrounding the instrument. This work is based on the history of mentalities and everyday life as a theoretical reference (Febvre, 1985; Duby, 1952; Bloch, 2022). This line of thought considers aspects ignored by the grand historical narratives, emphasizing everyday experiences. In this sense, it offers a qualitative study that allows us to outline the history of the piano in Barquisimeto between the 19th and 20th centuries.
Keywords: history of the piano; musical historiography; pianists; music education; Barquisimeto